PERKEMBANGAN KREATIVITAS BELAJAR MENGAJAR DI MASA PANDEMI - IKA; Siti Soliyah (PMPP Lembaga Penelitian dan Studi Kebijakan, 2022)
The impact of the Covid pandemic has made the world of education have and raise complex problems in Indonesia. With problems such as limited resource capabilities and the use of educational information technology infrastructure for each educator. For this reason, the development of teaching and learning creativity during the pandemic is very necessary. The purpose of this teaching and learning creativity is to find and implement and facilitate educators in the continuity of the teaching and learning process. There are so many ideas and ideas from some literacy that can be used as an alternative to providing education during this pandemic. With the renewal of education, it is strived to be more developed and more interested. With the implementation of learning that can be applied to the results of the diffusion of information technology by considering the subject and object and environmental conditions that are expected to produce good and fun learning habits. This research method is taken with a qualitative research method that analyzes several papers related to this title. The results obtained from the analysis of several papers that match this title are that the development of teaching and learning creativity in this pandemic period contains several concepts, ideas, ideas, strategies, and methods that can be used as alternatives during this pandemic, including: the